Conceptualization Family Muslim Modern: Synthesis Interpretation Bil Ma'tsur Ibn Katsir on Qs. Ali 'Imran :37 With Theory Miles - Liddinillah, Muhammad Yakhsyallah; Athoillah, Athoillah; Khosim, Ali (PT. Sharia Journal and Education Center, 2025)
This article explores the modern Muslim family concept by synthesizing Ibn Kathir's tafsir bil ma’tsur of Qur’an Surah Ali ‘Imran 37 with Robert Kiyosaki’s MILES theory (Money, Intelligence, Location, Education, Status). The verse portrays Maryam as accepted by God, raised in purity, and nurtured under Prophet Zakariya’s care. Ibn Kathir emphasizes early spiritual education and a religious environment in shaping children’s character. Using qualitative library research, this study draws on Ibn Kathir’s Tafsir al-Qur’an al-‘Azim, contemporary tafsir, and family education theories. Findings show that Ibn Kathir’s values align with MILES: Status in Imran’s family faith, Education and Intelligence in Zakariya’s guardianship, Money in divine sustenance for Maryam, and Location in the sacred mihrab. The synthesis offers a framework for modern Muslim families child education rooted in Qur’anic spirituality, reinforced by socio-economic resilience.